Education and Antisemitism in Elias Canetti’s Autobiography (Studia austriaca, 2020)
This article examines the textual discourse on antisemitism and education in Elias Canetti’s autobiography, in the passages set in his childhood and youth, thereby challenging approaches in Canetti research which risk masking the autobiographical presentation of antisemitism in Manchester, Vienna, Frankfurt and Zurich. Through these episodes the textual discourse promotes approaches to fighting antisemitism through education, both in terms of personal interventions and through institutions such as schools, so that citizens, and above all youth, do not fall prey to forms of hatred such as antisemitism.